YOUNG EYES ON ACCOUNTING. - Perry, Kenneth W. (The Accounting Review, 1958)
Abstract The article presents findings by the author on the progress made with respect to the distribution of a career pamphlet called "Young Eyes." The Task Committee on Student Personnel of the American Accounting Association was charged with the responsibility of preparing a career pamphlet describing the varied opportunities and depicting some of the challenges offered by the accounting profession. An article with the cooperation of the American Institute of Certified Public Accountants and the Institute of Internal Auditors, was published in January 1958 under the title "Young Eyes on Accounting," in an attempt to show what had been done so far and what it was hoped would be done in the future with Young Eyes. Two phases were decided by the Task Committee for distribution. In the first phase over two hundred editors of selected accounting, educational, and vocational periodicals were contacted and asked to run a news item on the nature and availability of Young Eyes. The second phase was one of following up and trying to maintain, and, wherever possible, increase the interest created during the initial phase. According to the findings 137, 340 copies of the pamphlet were distributed.